EFFECT OF BOOK TAX DIFFERENCES, INVENTORY TURNOVER AND FIRM SIZE ON PROFIT GROWTH - Habibah Habibah; Lyandra Aisyah Margie (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to examine the effect of book tax differences, inventory turnover and firm size on profit growth. This study uses a sample of real estate and property companies listed on the Indonesian stock exchange during the 2016-2021 period. The number of real estate and property companies that were used as research samples were 12 companies with 6 years of observation. This research sample used a purposive sampling method. Testing the hypothesis in this study using multiple regression analysis techniques with the help of SPSS software. The results of this study indicate that book tax differences, inventory turnover and firm size simultaneously have a significant effect on profit growth. While the results of research conducted partially show that book tax differences, inventory turnover and firm size have a significant effect on profit growth.